Aculeaxanthones A–E, new xanthones from the marine-derived fungus Aspergillus aculeatinus WHUF0198 - Wu, Jun; Shui, Hua; Zhang, Mengke; Zeng, Yida; Zheng, Mingxin; Zhu, Kong-Kai; Wang, Shou-Bao; Bi, Hongkai; Hong, Kui; Cai, You-Sheng (Frontiers in Microbiology, 2023)
Aculeaxanthones A−E (4−8), five new dimeric tetrahydroxanthones together with secalonic acid D (1), chrysoxanthones B and C (2 and 3), and 4−4'-secalonic acid D (9) have been isolated from Aspergillus aculeatinus WHUF0198. The structures of these compounds were elucidated on the base of 1D and 2D NMR and HR-ESIMS data, and the absolute configurations of the new xanthones 4−8 were determined by conformational analysis and time-dependent density functional theory-electronic circular dichroism (TDDFT-ECD) calculations. All the xanthones were evaluated for their cytotoxic activity against three human cancer cell lines, HCT-116, A549, and Bel-7402, and antimicrobial activity against Helicobacter pylori, Bacillus subtilis, and Staphylococcus aureus. Secalonic acid D (1) exhibited antibacterial activities against H. pylori G27, H. pylori 26695, H. pylori 129, H. pylori 159, S. aureus USA300, and B. subtilis 168 with MIC values of 4.0, 4.0, 2.0, 2.0, 2.0 and 1.0 μg/mL, respectively. Compound 6 showed significant bioactivity against Bel-7402 cell with an IC50 value of 1.96 μM.